Análisis, diseño e implementación de un sistema de información geográfico web turístico - Martinez, G. (2009)
In the competitive world in which we live today, technology has been fundamental basis for the creation of new applications that help make this growth will parallel the progression of time. Applications such as Geographic Information Systems changed its original objective of a tool for handling large amounts of information to an analysis tool for management orientation, becoming a Systems for Decision Making. This project shows the importance of developing a GIS application, such as digital tool for query and location of various tourist attractions of Guayaquil city, allowing amicably provide general knowledge of the streets, distances and routes displacement of habitants of the city to certain place. This tool lets collect and store through of a graphical interface, the media information centers and tourist points of the sectors defined in Guayaquil, as well as providing routes of origin / destination for the transfer of visitors according to the start address , destination address and road sense.